2013
DOI: 10.1109/tifs.2013.2278100
|View full text |Cite
|
Sign up to set email alerts
|

Compact Video Fingerprinting via Structural Graphical Models

Abstract: Much previous work in video fingerprinting has focused on robustness and security issues, but the compactness requirement, i.e., the hash should be of a short length with acceptable robustness and discriminability, continues to be a significant practical challenge. In this paper, we propose a video fingerprinting method with explicit attention on compactness. First, we develop a new graphical representation of the video which reduces temporal redundancies and makes robust feature extraction much more economica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…12-14. The results are in perfect agreement with those reported in [23] in the sense that CGO is significantly outperformed by the TIRI and SGM hashing techniques. It can be seen that CGO cannot withstand the applied attacks.…”
Section: B Identification Performancesupporting
confidence: 88%
See 3 more Smart Citations
“…12-14. The results are in perfect agreement with those reported in [23] in the sense that CGO is significantly outperformed by the TIRI and SGM hashing techniques. It can be seen that CGO cannot withstand the applied attacks.…”
Section: B Identification Performancesupporting
confidence: 88%
“…12). It has been reported that the strength of SGM lies in its ability to identify the video content when the bit budget of the hash is low [23]. However, with sufficiently large fingerprints, TIRI seems to perform slightly better than SGM according to our experimental results.…”
Section: B Identification Performancesupporting
confidence: 50%
See 2 more Smart Citations
“…In this way, feature extraction methods used over images can be applied in this signal representation. A Saliency Map (SM) is a kind of global feature widely used [12]- [14] that represents the most visual prominent regions of an image [15].…”
Section: Introductionmentioning
confidence: 99%